2001
DOI: 10.1046/j.1524-4733.2001.40202-168.x
|View full text |Cite
|
Sign up to set email alerts
|

Pid10: Effects of Linezolid on Hospital Length of Stay in Methicillin-Resistant Staphylococcus Infections Estimated From Multivariate Survival Analysis

Abstract: OBJECTIVES: To estimate differences in adjusted hospital length of stay (LOS) between linezolid and vancomycin using multivariate survival analysis. Linezolid's bioequivalent IV and oral formulations may enable earlier hospital discharge compared to vancomycin treatment. METHODS: 460 hospitalized patients with suspected/confirmed methicillin‐resistant Staphylococcus infections were treated with either linezolid (LZD) or vancomycin (VAN) in a randomized controlled trial. Covariate imbalances between treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…1). Of these studies, seven RCTs were excluded because they only studied the length of hospital stay and economic variables [20][21][22][23][24][25][26], four RCTs were excluded because they were part of RCTs already included in the meta-analysis and the data from these reports were used if additional useful information could be extracted [27][28][29][30], one RCT was excluded because it was written in Russian [31], one RCT was excluded because it was done in cancer patients [32] and one RCT was excluded because it had heterogeneity with other RCTs [33]. Thus, nine RCTs were included in the meta-analysis [34][35][36][37][38][39][40][41][42].…”
Section: Selected Randomised Controlled Trialsmentioning
confidence: 99%
“…1). Of these studies, seven RCTs were excluded because they only studied the length of hospital stay and economic variables [20][21][22][23][24][25][26], four RCTs were excluded because they were part of RCTs already included in the meta-analysis and the data from these reports were used if additional useful information could be extracted [27][28][29][30], one RCT was excluded because it was written in Russian [31], one RCT was excluded because it was done in cancer patients [32] and one RCT was excluded because it had heterogeneity with other RCTs [33]. Thus, nine RCTs were included in the meta-analysis [34][35][36][37][38][39][40][41][42].…”
Section: Selected Randomised Controlled Trialsmentioning
confidence: 99%
“…As in many health outcomes analyses, LOS was chosen as the primary endpoint in this analysis since it has significant implications for healthcare costs [7,15]. Increased resource use and costs associated with the treatment of methicillinresistant Gram-positive infections, particularly those caused by MRSA, are largely due to increased LOS and/or complications of therapy [7,8,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the mean and median LOS for the two treatment arms were obtained from Kaplan-Meier survival curves (duration analysis), a standard method for analysis of duration data that was also used in an earlier study [15], taking into account the censored LOS data. Differences between the survival curves for the two treatment arms were tested using the Wilcoxon Rank Sum Test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Further studies have also demonstrated reduction of length of hospital stay in patients with MRSA treated with linezolid [9,23] . Staphylococcus aureus is the single most common organism causing osteomyelitis secondary to trauma, surgery or insertion of a joint [24] . Chronic infection is notoriously difficult to treat.…”
Section: Joel J Et Al Linezolid In Orthopaedic Infectionsmentioning
confidence: 99%